Frequency reconfigurable slot antenna using metasurface for cognitive radio applications. Issue 3 (18th December 2019) - Chatterjee, Joysmita; Mohan, Akhilesh; Dixit, Vivek
Abstract : A dual‐port antenna system designed for cognitive radio applications is presented in this study. The structure comprises of an ultra‐wideband (UWB) sensing antenna and a reconfigurable communicating antenna. The former is a stepped slot structure with an offset feed, which covers the whole UWB frequency band from 3 to 10.6 GHz, whereas the latter is a dual‐band slot antenna (DBSA) fed with a fork‐shaped microstrip‐line feed and loaded with two identical layers of meandered metasurfaces (MSs). Frequency agility is realised by rotating the MS layers for the DBSA antenna. The dual‐band communicating antenna has three switchable states with tuning ranges of 28 and 45% in the lower‐ and upper‐frequency bands, respectively. The degree of isolation and gain in all three states are appreciable. The proposed structure is fabricated and measured, which has a good agreement with the simulated results.